The use of vermiculite as thermal insulation material - Seidaly Нуржан (Рroblems of engineering and professional education, 2023)
Currently in construction demand for environmentally friendly, highperformance thermal insulation materials is increased. To date, expanded vermiculite, which has unique properties such as low average density and thermal conductivity, is little used in ecological construction. Along with the decrease in the cost of heat conservation in buildings can solve such problems as their fire protection, sound reflection and sound absorption facilities, as well as several other problematic issues that arise in their accomplishment. To study the physical and mechanical properties of the gypsum-vermiculite-derived products for energy-efficient technologies. Apply modern technology in the production of gypsum and vermiculite.